Controllable Synthesis of Silver Nanoparticles Using Three-Phase Flow Pulsating Mixing Microfluidic Chip - Guojun Liu; Xiang Ma; Xiaodong Sun; Yanhui Jia; Tengfei Wang (Advances in Materials Science and Engineering)
On the basis of liquid-phase reduction mechanism, a novel synthesis method to prepare silver nanoparticles (AgNPs) is proposed, which uses piezoelectric-actuated three-phase flow pulsating mixing microfluidic chip. In order to study and explore the influence of different factors on the synthesis of AgNPs, a series of related synthesis experiments were carried out. The corresponding experimental conditions include the concentration of sodium hydroxide and reducing agent solution, polyvinylpyrrolidone (PVP) dosage, inlet flow rate, and synthesis temperature. The synthesized AgNPs were characterized by the UV-Vis absorption spectrophotometer and transmission electron microscopy. The effects of different experimental conditions on the controllable synthesis of AgNPs were analyzed, and the optimum synthesis conditions of AgNPs were obtained. Experimental results show that the spherical AgNPs with an average particle diameter of about 29 nm, high yield, fine morphology, and good monodispersity were synthesized using the microfluidic chip under the conditions of the working frequency (200 Hz), the initial concentration of silver nitrate (1 mM), the synthesis temperature (80°C), the concentration ratio of sodium hydroxide to silver nitrate (2 : 1), the concentration ratio of glucose to silver nitrate (4 : 1), the inlet flow rate (3.5 ml/min), and the quality ratio of PVP to silver (more than 1 : 1). The related research shows that it is an efficient synthesis method to develop the controllable synthesis experiments of AgNPs under multifactors using the three-phase pulsating mixing microfluidic chip.